The surgeon's daughter - Blake, Audrey, active 2020 (Sourcebooks Landmark, 2022)
"In the 19th century, women rarely study medicine. This means that Nora Beady, the only woman in her medical school, constantly feels like an outsider. And when she is chosen to work with the only female professor to develop the caesarian section, Nora draws the wrath of her male peers and professors. It's a dangerous-and divisive-procedure that could save countless lives and revolutionize women's health. But most doctors think it's too risky, many don't trust the findings of women, and husbands won't let their wives undergo the procedure. Nora knows her work is too important to give up. But when she meets a patient who will die without intervention, everything changes. Failure means proving the male medical establishment right and breaking her oath to do no harm. Everything is at stake: precious lives, Nora's career, and the role women will be allowed to play in medicine"--